2021
DOI: 10.1021/acsenergylett.1c01193
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Perovskite Solar Cells with High Power-Per-Weight: Progress, Application, and Perspectives

Abstract: In our day-to-day lives, advances in lightweight and flexible photovoltaics will promote a new generation of soft electronics and machines requiring high power-per-weight. Ultrathin flexible perovskite solar cells (F-PSCs) with high power-per-weight have displayed a unique potential for specific applications where lower weight, higher flexibility, and conformability are indispensable. This Review highlights the recent progress and practical applications of ultrathin and lightweight F-PSCs and demonstrates the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
91
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(97 citation statements)
references
References 164 publications
(329 reference statements)
0
91
0
Order By: Relevance
“…We choose PEN-ITO as our research electrode because PEN has a relatively higher thermal stability and photostability than other polymers. [18,32,33] A schematic diagram for the fabrication of the flexible transparent DARCs electrode was shown in Figure S1 (Supporting Information). The flexible electrode PEN-ITO was sandwiched between double-sided antireflection coatings, SiO 2 NPs on the PEN side and PMO composite film on ITO side.…”
Section: Resultsmentioning
confidence: 99%
“…We choose PEN-ITO as our research electrode because PEN has a relatively higher thermal stability and photostability than other polymers. [18,32,33] A schematic diagram for the fabrication of the flexible transparent DARCs electrode was shown in Figure S1 (Supporting Information). The flexible electrode PEN-ITO was sandwiched between double-sided antireflection coatings, SiO 2 NPs on the PEN side and PMO composite film on ITO side.…”
Section: Resultsmentioning
confidence: 99%
“…[47] The power-per-weight is defined by the ratio of the power output to device weight under standard solar radiation. [48] Song et al recently reported ultra-flexible (total thickness less than 3 µm) ternary OPVs with PCE of 15.5% and an outstanding powerper-weight of 32.07 W g −1 at a weight of 4.83 g m −2 . [26] Similar levels of power-per-weight have been reported for PSCs too, for instance Kang et al demonstrated ultra-flexible PSCs with powerper-weight of 29.4 W g −1 at a weight of 4.37 g m −2 and PCE of 12.85%.…”
Section: Emerging Pv Technologiesmentioning
confidence: 99%
“…Perovskite solar cells (PSCs) have received attention because their power conversion efficiency (PCE) has rapidly increased by over 25% [1,2]. Many researchers have tried to enhance the performance of PSCs and translate them from the laboratory to commercial products [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%